1994
DOI: 10.1038/bjc.1994.7
|View full text |Cite
|
Sign up to set email alerts
|

Stable bioenergetic status despite substantial changes in blood flow and tissue oxygenation in a rat tumour

Abstract: al., 1985;Evelhoch et al., 1986;Tozer et al., 1987; Vaupel et al., 1989a, b;Steen & Graham, 1991 (Bremner et al., 1993). The reduction in the oxygenation status caused by hydralazine is insufficient for detection by 31P-NMR in human xenografted tumours, whereas in RIF-1, SCCVII/Ha and KHT murine tumours large increases in the Pi/total phosphate ratio are found (Bremner et al., 1991;Adams et al., 1992). In the light of these discrepancies, a number of relevant issues need to be clarified regarding the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…The low tumour oxygenation is likely to be a consequence of both the increase in carboxyhaemoglobin and the reduction in blood flow, whereas the intact energy metabolism is most probably explained by a sufficient supply of glucose and/or other nutrients for anaerobic glycolysis even under these conditions. This hypothesis is supported by other studies showing that the tumour bioenergetic status was dependent on alterations in blood flow, oxygen availability (Vaupel et al, 1994a) and nutritional resources to sustain the energy metabolism (Gerweck et al, 1993). Using an in vitro assay and a different tumour model, it was demonstrated that the energy status was stable during oxygen deprivation but with the availability of sufficient glucose (Gerweck et al, 1993).…”
Section: Constant F-ntp/p In Hypoxic Tumourssupporting
confidence: 70%
“…The low tumour oxygenation is likely to be a consequence of both the increase in carboxyhaemoglobin and the reduction in blood flow, whereas the intact energy metabolism is most probably explained by a sufficient supply of glucose and/or other nutrients for anaerobic glycolysis even under these conditions. This hypothesis is supported by other studies showing that the tumour bioenergetic status was dependent on alterations in blood flow, oxygen availability (Vaupel et al, 1994a) and nutritional resources to sustain the energy metabolism (Gerweck et al, 1993). Using an in vitro assay and a different tumour model, it was demonstrated that the energy status was stable during oxygen deprivation but with the availability of sufficient glucose (Gerweck et al, 1993).…”
Section: Constant F-ntp/p In Hypoxic Tumourssupporting
confidence: 70%
“…Although nifedipine application during ILP increased tumour perfusion by approximately 60% (Figure 3) and in turn the nutrient and oxygen supply, only the glucose concentration in the tumour was elevated. Nifedipine had almost no impact on the bioenergetic status, a finding which is in good accordance to an earlier study demonstrating the energy status to be relatively stable despite substantial changes in blood flow and tissue oxygenation providing tumour perfusion does not fall below a certain threshold (Vaupel et al, 1994).…”
Section: Tumour Oxygenation and Oxygen Utilisationsupporting
confidence: 77%
“…However, the higher glycolytic rate had only a minor impact on the bioenergetic status resulting in ATP levels which are comparable to those found previously in untreated tumours (Vaupel et al, 1994). Although nifedipine application during ILP increased tumour perfusion by approximately 60% (Figure 3) and in turn the nutrient and oxygen supply, only the glucose concentration in the tumour was elevated.…”
Section: Tumour Oxygenation and Oxygen Utilisationsupporting
confidence: 59%
“…They argued that (an)aerobic glyco lysis is capable of maintaining the energy status. In vivo (DS sarcoma), Vaupel et al (1994) reported that after reduction of the tumour blood flow the amount of NTP remains nearly constant. These findings were explained by an intensified glycolysis due to the recruitment of glucose from the interstitial reservoir of the tumour.…”
Section: Discussionmentioning
confidence: 99%